G proteins, beta-adrenoreceptors and beta-adrenergic responsiveness in immature and adult rat ventricular myocardium: influence of neonatal hypo- and hyperthyroidism - Novotny, J; Bourová, L; Málková, O; Svoboda, P; Kolár, F (Journal of molecular and cellular cardiology, 1999)
Thyroid hormones influence a wide range of physiological responses and the heart is considered a major target organ for triiodothyronine action. In the present study we examined closely the presumed relationship between altered thyroid status in the newborn rat and maturation of the regulatory components of the myocardial hormone-sensitive adenylyl cyclase signaling system. Beta -adrenoceptors and the alpha subunits of the stimulatory (Gs) as well as inhibitory (Gi) G proteins were determined in ventricular myocardium of immature (21-day-old) hypo- or hyperthyroid rats and in adult (84-day-old) previously hypo- or hyperthyroid rats. The changes in receptor and G protein levels were correlated with basic parameters of cardiac function and inotropic responsiveness to isoproterenol. All results were compared with those obtained in age-matched controls. Hypothyroidism in immature rats was associated with markedly reduced myocardial beta-adrenoceptor density, lower content of the long isoform (Gsalpha-L) of the stimulatory G protein and increased amounts of Gialpha2 and Gialpha3. These changes were accompanied by substantially diminished sensitivity to the inotropic effect of isoproterenol. On the other hand, no change in beta-adrenoceptor number, an increased level of Gsalpha-L and decreased levels of Gialpha2 were found in hyperthyroid myocardium. Cardiac inotropic responsiveness to isoproterenol in immature hyperthyroid rats was not significantly altered. In adult hearts of previously hyper- or hypothyroid rats, beta-adrenoceptor density was decreased but G protein levels as well as functional response were comparable to those determined in control animals. It may be concluded that physiological level of thyroid hormones is an important modulator of the normal maturation of the beta-adrenergic system in the developing rat ventricular myocardium. In adult rats previously affected by altered thyroid status, the function of their myocardial beta-adrenergic signaling appears to be compensated despite a lower number of the receptors.
Keywords: adenylátcyklasy; Myocardial Contraction; signální transdukce; Signal Transduction; techniky in vitro; beta-adrenergní receptory; Hypothyroidism; krysa rodu Rattus; proteiny vázající GTP; Adenylyl Cyclases; zvířata; potkani Wistar; Adrenergic beta-Agonists; Isoproterenol; hypotyreóza; Rats, Wistar; Receptors, Adrenergic, beta; Male; agonisté adrenergních beta-receptorů; Heart Ventricles; kontrakce myokardu; Hyperthyroidism; In Vitro Techniques; Rats; myokard; Animals; Myocardium; mužské pohlaví; isoprenalin; srdeční komory; GTP-Binding Proteins; hypertyreóza